Cardiovascular toxicities associated with chimeric antigen receptor T-cell therapy - Liu, Jia-Hui; Liu, Kun-Yao; Zhao, Xiang; Zhou, Xin; Jiang, Yichuan (Frontiers in Pharmacology, 2025)
Chimeric antigen receptor (CAR) T-cell therapy has emerged as a groundbreaking immunotherapeutic approach, particularly for oncohematological patients who are refractory to conventional treatments. As clinical trials expand the applications of CAR T-cell therapy beyond hematologic malignancies, a critical understanding of its associated toxicities, particularly cardiovascular complications, becomes imperative. This review synthesizes current literature on the interplay between cytokine release syndrome (CRS) and cardiotoxicity related to CAR T-cell therapy, emphasizing the potential severity of these adverse events. While significant progress has been made in managing CRS, the cardiac manifestations—ranging from mild events to life-threatening complications—remain underreported in pivotal studies. We explore the incidence and nature of cardiotoxicity in real-world and clinical trial settings, identify risk factors contributing to cardiovascular events, and propose guidelines for pre-therapy evaluations, post-infusion monitoring, and management strategies. By highlighting the urgent need for heightened awareness and proactive care, this review aims to enhance patient safety and optimize outcomes in the evolving landscape of CAR T-cell therapy.